2023
DOI: 10.1159/000529240
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and Objective Assessment of Chewing Performance in Older Adults with Different Dental Occlusion

Abstract: Objectives: Satisfactory masticatory function is a significant indicator of improved oral health related quality of life in older adults, either with or artificial teeth. The purpose of this study was to examine masticatory performance of older adults with different prostho-dontic reconstructions and occlusion, as well as to compare subjective and objective as-sessment of chewing performance. Material and Methods: This study included 100 partici-pants aged 65 and more. The chewing function questionnaire (CFQ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
(46 reference statements)
1
3
0
Order By: Relevance
“…22 Although the validity of each question of poor oral function that was used in the present study was not confirmed previously, previous studies reported the validity of similar questions for subjective chewing ability, subjective swallowing problems, and xerostomia, and they reflected clinical measurements. [23][24][25] In addition, a previous study reported that individuals who answered as having chewing difficulty in the question employed in the present study also had worsened objective chewing ability. 26 For each single-/two-/three-time-point exposure data point, each exposure was evaluated for 2010, 2010-2013, and 2010-2013-2016, respectively.…”
Section: Exposure Variablessupporting
confidence: 54%
See 1 more Smart Citation
“…22 Although the validity of each question of poor oral function that was used in the present study was not confirmed previously, previous studies reported the validity of similar questions for subjective chewing ability, subjective swallowing problems, and xerostomia, and they reflected clinical measurements. [23][24][25] In addition, a previous study reported that individuals who answered as having chewing difficulty in the question employed in the present study also had worsened objective chewing ability. 26 For each single-/two-/three-time-point exposure data point, each exposure was evaluated for 2010, 2010-2013, and 2010-2013-2016, respectively.…”
Section: Exposure Variablessupporting
confidence: 54%
“…These questions were included in a validated questionnaire for screening frailty among older Japanese adults (Kihon checklist) 22 . Although the validity of each question of poor oral function that was used in the present study was not confirmed previously, previous studies reported the validity of similar questions for subjective chewing ability, subjective swallowing problems, and xerostomia, and they reflected clinical measurements 23–25 . In addition, a previous study reported that individuals who answered as having chewing difficulty in the question employed in the present study also had worsened objective chewing ability 26 .…”
Section: Methodsmentioning
confidence: 62%
“…The loading forces of 50, 100, and 150 N, respectively, were chosen based on reports of the minimum and maximum biting forces in individuals with conventional complete dentures, implant-supported ODs, and natural teeth [ 43 , 44 , 45 , 46 , 47 ]. The forces used represent the average forces in subjects wearing implant ODs.…”
Section: Discussionmentioning
confidence: 99%
“…These may relate to differences in predominant chewing side, jaw geometry, teeth shape, oral status, and sensitivity to pain or food texture, such as rheological behavior, hardness, and adhesion, especially dentures. Furthermore, reducing the number of natural teeth, particularly posterior teeth, gradually diminishes chewing capacity and escalates challenges in mastication [ 55 ]. However, the results can be reproducible and stable over time.…”
Section: Discussionmentioning
confidence: 99%